2013
DOI: 10.1002/cjg2.20012
|View full text |Cite
|
Sign up to set email alerts
|

Interdecadal Linkages Between the Pacific Decadal Oscillation and Interhemispheric Air Mass Oscillation and Their Possible Connections with East Asian Monsoon

Abstract: The Pacific decadal oscillation (PDO) recently emerged in the literature as a robust signal in the Northern Hemisphere climate variability. Many studies reported that the relationships between PDO and East Asian monsoon (EAM) and climate variability in China are significant. Their possible mechanisms are, however, still unclear. Using the observational NCEP/NCAR reanalysis and Chinese station data during the period of 1969–2008, this study investigates the interdecadal relationship between Pacific decadal osci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Data availability. We analyzed the transition process of the PDO using data from the National Oceanic and Atmospheric Administration (NOAA), available at: https://psl.noaa.gov/gcos_wgsp/ Timeseries/Data/pdo.long.data (last access: October 2020; Mantua et al, 1997).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data availability. We analyzed the transition process of the PDO using data from the National Oceanic and Atmospheric Administration (NOAA), available at: https://psl.noaa.gov/gcos_wgsp/ Timeseries/Data/pdo.long.data (last access: October 2020; Mantua et al, 1997).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In this paper, three ideal time sequences are tested to study the prediction method. The prediction method is also applied to study the climate transition process of the PDO, which is an important signal that reveals climatic variability on the decadal timescale (Mantua et al, 1997;Barnett et al, 1999;Zhang et al, 1997;Yang et al, 2004). Previous studies (Lu et al, 2013;Trenberth and Hurrell, 1994) have indicated that there have been many abrupt changes in the PDO over the past 100 years.…”
Section: Introductionmentioning
confidence: 99%
“…However, attribution of these observed precipitation trends to global warming is challenging, given the interference of internal decadal-to-multi-decadal variations in the climate system such as the Interdecadal Pacific Oscillation (IPO) and/or the Atlantic Multidecadal Oscillation (AMO) (e.g., Cai et al, 2022;Du et al, 2022;F. Liu et al, 2021;Gu et al, 2023;Han et al, 2016;Lu et al, 2013;T. Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In eastern China, the northern part becomes drier, while the southern part becomes wetter in recent decades (e.g., C. Wang et al., 2012; M. Li et al., 2022; Pei et al., 2015). However, attribution of these observed precipitation trends to global warming is challenging, given the interference of internal decadal‐to‐multi‐decadal variations in the climate system such as the Interdecadal Pacific Oscillation (IPO) and/or the Atlantic Multidecadal Oscillation (AMO) (e.g., Cai et al., 2022; Du et al., 2022; F. Liu et al., 2021; Gu et al., 2023; Han et al., 2016; Lu et al., 2013; T. Li et al., 2021). The long‐term land use changes and the limited length of the instrumental record, among other factors, can also influence the attribution (e.g., D. Li et al., 2017; Du et al., 2022; Roxy et al., 2015; Turner & Annamalai, 2012; Yan et al., 2020).…”
Section: Introductionmentioning
confidence: 99%